2019
DOI: 10.1002/chir.23060
|View full text |Cite
|
Sign up to set email alerts
|

1‐Hydroxymethyl‐7‐oxabicyclo[2.2.1]hept‐2‐ene skeleton in enantiopure form through enzymatic kinetic resolution

Abstract: Lipase-catalysed enantioselective acetylation and deacetylation routes were investigated to prepare 1,5,6-trisubstituted 7-oxabicyclo[2.2.1]hept-2-ene skeleton in enantio-pure form. The racemic alcohol (6) used in acetylation reaction was accessed through Diels-Alder reaction of TBDMS-protected furfuryl alcohol with maleic anhydride, followed by reduction-benzylation-desilylation sequence. After systematic screening of lipases and solvents, Candida antarctica B on acrylic resin in pentane was identified as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 84 publications
(109 reference statements)
0
1
0
Order By: Relevance
“…We investigated the enzyme-assisted interfacial regioselective ester hydrolysis of synthetic ONB-based amphiphiles . Moreover, our research explored lipase-catalyzed acetylation and deacetylation processes aimed at achieving the enantiopure form of the ONB headgroup . In our most recent studies, the ONB-based synthetic lipids were investigated as novel drug delivery carriers for anticancer drugs. , The cell viability and hemolytic assays revealed that ONB-based lipids have a good safety profile.…”
Section: Introductionmentioning
confidence: 99%
“…We investigated the enzyme-assisted interfacial regioselective ester hydrolysis of synthetic ONB-based amphiphiles . Moreover, our research explored lipase-catalyzed acetylation and deacetylation processes aimed at achieving the enantiopure form of the ONB headgroup . In our most recent studies, the ONB-based synthetic lipids were investigated as novel drug delivery carriers for anticancer drugs. , The cell viability and hemolytic assays revealed that ONB-based lipids have a good safety profile.…”
Section: Introductionmentioning
confidence: 99%